Pengembangan Media Pembelajaran Multimedia Peka (Pembagian Perkalian) Pada Materi Pembagian Dan Perkalian Mata Pelajaran Matematika Siswa Kelas III SD - Yusifa Dyan Azhari; Sutrisno Sahari; Karimatus Saidah (Departement of Mathematics Education, 2023)
This research is motivated by the problems that exist in SDN Gayam 3, which shows the learning of Mathematics in the basic competencies of subtraction and addition in grade III. In this study using the RnD (Research and Development) method. The development model used is the ADDIE research model which has 5 stages, namely : (1) Analysis Stage, (2) Design Stage, (3) Development Stage, (4) Implementation Stage, (5) Evaluation Stage. The subjects of this study were 29 students of grade III SDN Gayam 3 Kediri city. The data analysis technique used is descriptive qualitative analysis and quantitative descriptive analysis. The result of this study indicate that (1) the validation results obtained from the media validator reach a percentage of 86,66% and the validator material 91%. Then the results of the validity an average percentage of 89%. So that devepment media can be declared valid. (2) The results of the teacher’s response questionnaire rechead a percentage of 88,5%. So that media development is declared practical. (3) The results of the analysis of limited trials and wide trials of post test questions reached 83 and 88,4, there is a significant difference through the Paired T-Test. So that the development of PEKA media is stated to be effective for use.